Analisis penggunaan media pendingin pada proses pendinginan perunggu gamelan Bali - Sugita, I Ketut Gede; Priambadi, IGN; Putri Kusuma K, Cok Istri (Jurnal Energi Dan Manufaktur; Vol 2, No.1 Juni 2007, 2012)
The process of making Bali Music Instrument (Gamelan Bali) included moulding, forging, adjustment of harmony (called sruti), and finally finishing process. In commonly application, there were some different media that used in the cooling process, however generally water was used as cooling media. The cooling media has an important effect on mechanical property of the materials. The aim of this research is to investigate the effect of cooling media on mechanical properties of Gamelan Bali. The specimens are the casting product between copper and tin with compotition 80%Cu – 20%Sn. The treatment on specimen comprised machining process, heating to 500°C in an electrical furnace followed by 60 minute holding time. The cooling process was conducted with the cooling media of water, oil, and air, respectively. The crack toughness testing was then applied by using an ASTM E 399-90 standard test machine. The results showed that the cooling with water resulted in the highest crack toughness; on the contrary the air resulted in the lowest.
Keywords: Crack toughness, holding time, macro and micro structure, cooling media